Research progress on curved plates in China: Mechanical analysis methods and load-bearing behaviours. (May 2022) - Song, Yiheng; Lin, Qinyu; Chen, Jinxiang
Highlights: Several mechanical analysis methods and their characteristics are summarized. Stability and dynamic traits of solid and reticulated curved plates are clarified. Research directions of testing methods, classification, etc. are pointed out. Several foci are given, such as the development of multi-functional curved plates. Abstract: To support the effective development of curved plates, this paper focuses on research progress in China on the associated mechanical analysis methods and load-bearing behaviours. For the former, three main categories exist: numerical simulation methods, the use of existing equipment to develop corresponding fixtures, and the use of advanced digital image processing technologies. Among them, the "height adjustment method" and the testing method involving splicing two curved plates into a box according to symmetry based on shear stability tests are expected to predominate in industry. Regarding load-bearing behaviours, the focus is currently on the stability and dynamic performance of solid-type and reticulated curved plates. Finally, for various complex curved plates or curved bodies, an important future research direction will be the establishment of a classification system for testing methods based on actual engineering features, such as the plate type (internal structure), load conditions, and material category, which can be used to reveal the load-bearing properties and common features of various curved plates and formulate corresponding tests, quality standards and specifications. In particular, lightweight and high-strength structures, such as honeycomb/beetle elytron core multifunctional curved plates made of aluminium and paper, are expected to receive widespread research attention in this area.